Dietary Habits and Nutritional Knowledge among Primary School Children in Fayoum Governorate (International Journal of Studies in Nursing, 2019)
Background and aim: Improving the eating habits of children is essential to reduce the future burden of non-communicable illnesses. Nutritional diseases affect higher than 30% of school age children. This study aimed to assess the dietary habits and nutritional knowledge among primary school age children in Fayoum Governorate, Egypt. Study design: A cross-sectional descriptive design was utilized. Setting: The study was implemented in three governmental mixed primary schools in EL-Fayoum city; Egypt, that were selected randomly. Sample: Cluster random sample techniques used for selecting of the study group consisted of 300 students aged from 10-12 years for both sexes attending grade five and six. Tools: three tools of data collection consisted of: 1- self-administered questionnaire comprised socio-demographic data of the students and parents, and students’ knowledge about nutrition, 2- the students’ dietary habits as consumption of the breakfast, drinking water, 3- Health assessment sheet to assess the students’ nutritional status including weight, height, BMI, and appearance. The study findings revealed that 69.3% of the study group were underweight, 36.3% were stunted, and 6.7%, 3.3% were overweight and obese respectively. About 45% had fair knowledge while 34% had good knowledge about the nutrition. More than half of the students had unhealthy dietary behavior and appearance. There was a statistically significant difference (P: 0